Gospodarjenje z jelko v Sloveniji - Bončina, Andrej (Zbornik gozdarstva in lesarstva, 2009)
In the paper, we analysed the structure and developmental characteristics of forest stands with silver fir in Slovenia, the management and cut in four forest site strata, where silver fir occurs. We used databases from the Slovenia Forest Service. In growing stock (GS) of silver fir, large (dbh=30-49cm) and very large (d=50 cm and more) diameter trees account for 84.9 % at the national level. The highest share of very large diameter silver fir trees (45 %) is in Dinaric silver fir forests and silver fir-beech forests(B), the lowest in silver fir forests with fern and silver fir forests on non-carbonate ground (C). The dbh structure of GS, number of silver fir trees recorded from two subsequent measurements from permanent sampling plots,rising mean dbh of harvested silver fir trees all indicate general agingand regression of silver, which is typical of stratum B but not in all other strata. The ingrowth of silver fir in 10 years is highest in stratum C (19.2 trees/ha), the lowest in B (4.2 trees/ha). In the latter, cut intensity (22.3 % of GS), the mean dbh of harvested silver firs are highest, too. For active conservation of silver fir, reduction of the impact of large ungulates and differentiated silviculture with longer regeneration periods is of crucial importance. Some other measures are also suggested.
Keywords: Abies alba Mill.; jelka; jelovi gozdovi; rast; razvoj; Slovenia; Slovenija; struktura